Impact of International Accreditation in Pharmacy Education: Pharmacy School Students’ Perspective - Darwish, Rula; Saleh, Mohammad; Ammar, Khawlah; AlMasri, Mohammad (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: The accreditation of undergraduate Pharmacy Schools is an important quality assurance process. In spite of the widespread adoption of international accreditation processes and an increasing attention on accreditation as a mechanism to ensure minimum standards are met, there is little evidence to support their effectiveness. Objectives: To assess the School of Pharmacy students’ and new graduates’ views on the impact of international certification on their education and career and whether this experience could be used to improve the pharmacy education program and environment. Methods: A descriptive cross-sectional survey was used with six major themes focusing on, student-faculty-administration relationships, student support, learning environment and pedagogical methods, library and electronic learning resources, experiential training and the educational program as a whole. Four hundred forty-nine participants completed the survey from which fifty-two were new graduate. Results: School of Pharmacy students’ and new graduates have positive perception of international certification. Participants agreed that the certification process has been beneficial in terms of enhancing the overall program quality, the quality of education, learning environment, program structure, students support as well as enhancing opportunities. Misperceptions, however, existed about potential opportunities available to graduates of internationally certified programs. Conclusion: This research carries value to university administrators and education policymakers in terms of improving regulations and targeting students to ensure promising academic environment and improve the image of the educational institutions.
Keywords: Accreditation; International certification; Pharmaceutical education; Students; Pharmacy; Learning environment